Early assessment: part of a bigger plan towards first-year success? - van Schalkwyk, S; Young, G; Ruiters, J; Farmer, J (South African Journal of Higher Education, 2016)
At Stellenbosch University all first-year students complete an assessment task during the first six weeks of the academic year. Results are made available online to students and staff almost immediately and in response various student support interventions and enhanced learning opportunities are made available to students who are identified as potentially being at-risk. This article draws on student responses obtained during an investigation that was conducted to discern how they experience the system known as Early Assessment. Nine student focus group interviews were conducted. Qualitative thematic analysis of the transcribed data revealed a picture of how Early Assessment is perceived, highlighting a considerable diversity in the way it is being applied resulting in a range of experiences for the students and leading to a variety of responses on their part. This diversity of understanding and experience similarly influence the students’ subsequent learning in both positive and negative ways. While many students described how the Early Assessment changed their approaches to learning and contributed to their success, others described it as being too easy or unrelated to summative assessment tasks. We conclude by highlighting the importance of the role of effective assessment planning and the careful co-ordination thereof.